Blood pressure and heart rate related to sex in untreated subjects: the India ABPM study. Issue 7 (17th June 2020) - Kaul, Upendra; Bhagwat, Ajit; Omboni, Stefano; Pancholia, Arvind K.; Hardas, Suhas; Bardoloi, Neil; Davidson, Deepak; Sivakadaksham, Peruvamba R.; Mohan, Jagdish C.; Vaidyanathan, Peruvamba R.; Natarajan, Subramaniam; Kapardhi, Lakshnmi N. P.; et al.
Abstract: Women are underrepresented in groups of patients seeking hypertension care in India. The present paper reports trends in office and ambulatory blood pressure measurement (OBPM, ABPM) and 24‐h heart rate (HR) with sex in 14, 977 subjects untreated for hypertension (aged 47.3 ± 13.9 years, males 69.4%) visiting primary care physicians. Results showed that, for systolic blood pressure (SBP), females had lower daytime ABPM (131 ± 16 vs. 133 ± 14 mm Hg, P  < .001) but higher nighttime ABPM (122 ± 18 vs. 121 ± 16 mm Hg, P  < .001) than males. Females had higher HR than men at daytime (80 ± 11 vs 79 ± 11.5 bpm) and nighttime (71 ± 11 vs 69 ± 11), respectively (all P  < .001). Dipping percentages for SBP (7.4 ± 7.3 vs 9.3 ± 7.4%), DBP (10.1 ± 8.6 vs. 12.3 ± 8.9%), and HR (10.7 ± 7.9 vs. 12.8 ± 9.2%) were lower ( P  < .001) for females than for males, respectively. Females more often had isolated nighttime hypertension as compared to males (14.9%, n = 684% vs 10.6%, n = 1105; P  < .001). BP patterns and HR showed clear differences in sex, particularly at nighttime. As females were more often affected by non‐dipping and elevated nighttime SBP and HR than males, they should receive ABPM, at least, as frequently as men to document higher risk necessitating treatment.